Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.341
|View full text |Cite
|
Sign up to set email alerts
|

SLEDGE-Z: A Zero-Shot Baseline for COVID-19 Literature Search

Abstract: With worldwide concerns surrounding the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), there is a rapidly growing body of scientific literature on the virus. Clinicians, researchers, and policymakers need to be able to search these articles effectively. In this work, we present a zeroshot ranking algorithm that adapts to COVIDrelated scientific literature. Our approach filters training data from another collection down to medical-related queries, uses a neural reranking model pre-trained on scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This evidence is backed up by following scholarly publications [108,109,110,111,112,113,114,115,116,117,118,119]. I first demonstrated that neural techniques can produce effective ranking models (Hypothesis 1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This evidence is backed up by following scholarly publications [108,109,110,111,112,113,114,115,116,117,118,119]. I first demonstrated that neural techniques can produce effective ranking models (Hypothesis 1).…”
Section: Discussionmentioning
confidence: 98%
“…Parts of Chapters 2-5 are reproductions of my jointly authored publications [108,109,110,111,112,113,114,115,116,117,118,119].…”
Section: Organizationmentioning
confidence: 99%
“…Removing documents published before 2020 (or when the pandemic began to gain widespread notice) had been previously suggested by McAvaney et al in their post-hoc analysis of their neural re-ranking system as a possible method to improve performance. 24…”
Section: Methodsmentioning
confidence: 99%
“…The output of Pyserini is then reranked by a T5 language model, 10 which is fine-tuned on MS MARCO, a large machine reading comprehension dataset. 18 Similarly, SLEDGE 19 uses a similar approach, but using SciBERT 13 to rerank documents.…”
Section: Background and Significancementioning
confidence: 99%